Mid-Atlantic U.S. Offshore Carbon Storage Resource Assessment. (July 2017) - Cumming, Lydia; Gupta, Neeraj; Miller, Kenneth; Lombardi, Christopher; Goldberg, David; ten Brink, Uri; Schrag, Daniel; Andreasen, David; Carter, Kristin
Abstract: Attention to offshore prospects for geologic storage of carbon dioxide (CO2 ) in the U.S. is required to address numerous large point sources located along the U.S. Atlantic Coast. Research is underway to develop a reliable method for screening candidate storage formations with the greatest potential for effective, permanent storage of CO2, and producing data-driven regional-scale estimates of the prospective CO2 storage resource that exists offshore of the Mid-Atlantic U.S. This paper introduces the Mid-Atlantic U.S. Offshore Carbon Storage Resource Assessment project, describes the technical approach to achieve project goals, and presents preliminary results. The existing data set and challenges for data collection and analysis also are discussed.